Strengthening Student Learning Motivation in Fiqh Subjects Through the Adolescent Psychology Approach - Suharnis Suharnis; Rustina Rustina; Sjakir Lobut; Rusdin Rusdin (AL-ISHLAH: Jurnal Pendidikan, 2023)
In today’s young generation, there is an understanding of religion that is starting to disappear among the younger generation. To solve this problem, it is necessary to motivate the younger generation to be able to study fiqh science. This research was carried out to describe how important the application of adolescent psychology is in increasing the learning motivation of students at a state Madrasah Aliyah Negeri in Palu. This research was carried out using a qualitative approach. Interviews was employed to collect the data. Meanwhile, the data analysis process carried out in this study used deductive and inductive techniques. The results of this study then found that learning motivation for students was strongly influenced by their psychological development. Therefore, problems in fiqh learning activities can be solved by increasing student motivation through an adolescent psychology approach. Through this, it is hoped that students will want to learn fiqh.